Situs Inversus Totalis: A Rare Congenital Anomaly and the Presence of COPD Giving a Concept of Dextroposition with Limb Lead Reversal in ECG - Sabah, Khandker Md. Nurus; Chowdhury, Abdul Wadud; Islam, Mohammad Shahidul; Amin, Mohammad Gaffar; Khandakar, Md Azizul Hassan; Kawser, Shamima (Bangladesh Heart Journal, 2017)
Situs inversus totalis is the mirror-image of normal position of the thoracic and abdominal viscera. It may be detected incidentally when the patient seek medical attention for other medical illness. From medico-legal points of view, this rare disorder is important in many ways for a junior physician to prevent a big mishap, especially surgical. Here, we report a case, who was 55- year-old, seeking medical attention for infective exacerbation of chronic obstructive pulmonary disease incidentally diagnosed as a case of situs inversus totalis. Bangladesh Heart Journal 2016; 31(2) : 100-103